Elsbeth In Taxland, or Through the Change Purse: An Appreciation - Bryden, P. (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2019)
This reflection on E. A. Heaman’s Tax, Order, and Good Government: A New Political History of Canada, 1867-1917 suggests that the innovative “taxationist” interpretation of Canada the author offers bears some striking similarities to other upside-down worlds.  Like Alice’s Wonderland, Bryden shows that this new view of Canada has all manner of interesting characters, new ways of looking at old subjects, and new vantage points from which to observe the familiar.